Microstructural Dynamics of the Myocardium: Orientation of the Muscle Fibers and Occurrence of Cardiomyopathies - René Thierry Djoumessi; François Beceau Pelap (Advances in Materials Science and Engineering, 2022)
This paper considers the Holzapfel–Ogden (HO) model to examine the behavior of the left ventricle myocardium. At the tissue level, we analyze the contributions of the orientation angle of muscle fibers (MFs) and investigate their effects on the occurrence of certain cardiomyopathies and congenital diseases at the organ level. Knowing the importance of myocardial microstructure on cardiac function, we vary the angle between the direction of collagen sheets and MFs in all layers of the myocardium (from epicardium to endocardium) to model the effects of tilted MFs. Based on the HO model in which the directions of the fibers are orthogonal and using the strain energy of HO, we construct a tensile-compression test and simulate the dynamics of a cubic sample. We recover the authors’ results exhibiting the existence of residual stresses in various directions. Then, we modify the energy of HO slightly to assess the impact of the same stress states on the system with tilted MFs. A numerical tensile-compression test performed on this new cubic sample shows that, in certain directions, the heart tissue is more resistant to shear deformations in some planes than in others. Moreover, it appears that the residual stress is smaller as the angle of orientation of the MFs is small. Furthermore, we observe that the residual stress is greater in the new model compared to the normal HO model. This could affect the heart muscle at the organ level leading to hypertrophied/dilated cardiomyopathy.